(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
The study analyzed the marketing of chilli pepper in selected markets in Sumaila local government Kano State, Nigeria. The study focused on the socioeconomic characteristics of the chilli pepper marketers, profitability and marketing efficiency of chilli pepper as well as constraints of chilli pepper marketing. The result of socioeconomic characteristics showed that majority of the chilli pepper marketers (96.2%) were male and 46.2% were between the ages of 30-39years, and the majority of the marketers had attended various level of education in the study area which means they can read and write. The results showed that 69.8% of the sampled marketers have less than 10 people in their household. The result further revealed that 49.1% of the marketer’s haves less 10 years’ experience in the marketing of chilli pepper in the study area. Chilli pepper marketing was profitable venture with a net margin of 2,520.74 per 30kg of bag. Marketing of chilli pepper was found to be efficient in view of the high marketing efficiency obtained. The result revealed that the constraints faced by chilli pepper marketers were lack of uniform measure, poor credit facilities, transportation, inadequate storage facilities and poor market infrastructures. It can be concluded that pineapple marketing was profitable and efficient in the study area despite the constraints faced by the marketers. And therefore can be recommended that Construction of good road network to reduce damage of pineapple during transportation and plastics trays should be provided